Design of metamaterials biosensor antenna for the rapid detection of coronaviruses COV-19 (SARS2) - Fechkeur, Meriem; Latar, Kaouthar; Bensafiddine, Djalal Eddine (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2021)
Our thesis consist of proposing a new technique of utilizing metamaterials biosensor antenna for rapid diagnosis of coronavirus SARS-COV-2 in human blood samples. This biosensor was designed numerically by evaluating the variations in the reflection coefficient (S11) and others parameters such as the realized gain and the bandwidth. Two different metallic conductor of our metamaterials structure has been used for analyses the sensibility of our biosensor antenna devices. For the metamaterials based on copper as a metallic conductor, we showed that in the case of COVID-19 blood, the resonance frequency shifted towards higher frequency band by about 100 MHz compared to the normal blood filled sensor. The maximum return loss contrast between the normal blood and COVID-19 blood filled sensor is about 3.64 dB. For the metamaterials based on graphene as a metallic conductor, there was a contrast of about 6.78 dB in the magnitude of the return loss between the normal blood and COVID-19 blood filled sensor. These results are hoped to help physicians and clinical microbiologists to address the challenge for effective detection of COVID-19.
Option : Systèmes de Télécommunication